Hydroponic Solutions for Soilless Production Systems: Issues and Opportunities in a Smart Agriculture Perspective - Sambo, Paolo; Nicoletto, Carlo; Giro, Andrea; Pii, Youry; Valentinuzzi, Fabio; Mimmo, Tanja; Lugli, Paolo; Orzes, Guido; Mazzetto, Fabrizio; Astolfi, Stefania; Terzano, Roberto; Cesco, Stefano (Frontiers in Plant Science, 2019)
Soilless cultivation represent a valid opportunity for the agricultural production sector, especially in areas characterized by severe soil degradation and limited water availability. Furthermore, this agronomic practice embodies a favorable response toward an environment-friendly agriculture and a promising tool in the vision of a general challenge in terms of food security. This review aims therefore at unraveling limitations and opportunities of hydroponic solutions used in soilless cropping systems focusing on the plant mineral nutrition process. In particular, this review provides information (1) on the processes and mechanisms occurring in the hydroponic solutions that ensure an adequate nutrient concentration and thus an optimal nutrient acquisition without leading to nutritional disorders influencing ultimately also crop quality (e.g., solubilization/precipitation of nutrients/elements in the hydroponic solution, substrate specificity in the nutrient uptake process, nutrient competition/antagonism and interactions among nutrients); (2) on new emerging technologies that might improve the management of soilless cropping systems such as the use of nanoparticles and beneficial microorganism like plant growth-promoting rhizobacteria (PGPRs); (3) on tools (multi-element sensors and interpretation algorithms based on machine learning logics to analyze such data) that might be exploited in a smart agriculture approach to monitor the availability of nutrients/elements in the hydroponic solution and to modify its composition in realtime. These aspects are discussed considering what has been recently demonstrated at the scientific level and applied in the industrial context.